Aortic dilatation in Marfan syndrome: role of arterial stiffness and fibrillin-1 variants. Issue 1 (January 2018) - Salvi, Paolo; Grillo, Andrea; Marelli, Susan; Gao, Lan; Salvi, Lucia; Viecca, Maurizio; Di Blasio, Anna Maria; Carretta, Renzo; Pini, Alessandro; Parati, Gianfranco
Abstract : Objective: Marfan syndrome (MFS) is an autosomal dominant genetic disorder characterized by aortic root dilation and dissection and an abnormal fibrillin-1 synthesis. In this observational study, we evaluated aortic stiffness in MFS and its association with ascending aorta diameters and fibrillin-1 genotype. Methods: A total of 116 Marfan adult patients without history of cardiovascular surgery, and 144 age, sex, blood pressure and heart rate matched controls were enrolled. All patients underwent arterial stiffness evaluation through carotid–femoral pulse wave velocity (PWV) and central blood pressure waveform analysis (PulsePen tonometer). Fibrillin-1 mutations were classified based on the effect on the protein, into 'dominant negative' and 'haploinsufficient' mutations. Results: PWV and central pulse pressure were significantly higher in MFS patients than in controls [respectively 7.31 (6.81–7.44) vs. 6.69 (6.52–6.86) m/s, P  = 0.0008; 41.3 (39.1–43.5) vs. 34.0 (32.7–35.3) mmHg, P  < 0.0001], with a higher age-related increase of PWV in MFS (β 0.062 vs. 0.036). Pressure amplification was significantly reduced in MFS [18.2 (15.9–20.5) vs. 33.4 (31.6–35.2)%, P  < 0.0001]. Central pressure profile was altered even in MFS patients without aortic dilatation. Multiple linear regression models showed that PWV independently predicted aortic diameters at the sinuses of Valsalva (ß = 0.243, P  = 0.002) and at the sinotubular junction (ß = 0.186, P  = 0.048). PWV was higher in 'dominant negative' than 'haploinsufficient' fibrillin-1 mutations [7.37 (7.04–7.70) vs. 6.60 (5.97–7.23) m/s, P  = 0.035], although this difference was not significant after adjustment. Conclusion: Aortic stiffness is increased in MFS, independently from fibrillin-1 genotype and is associated with diameters of ascending aorta. Alterations in central hemodynamics are present even when aortic diameter is within normal limits. Our findings suggest an accelerated arterial aging in MFS. Abstract : Supplemental Digital Content is available in the text